Design synthesis and structural optimization of a lightweight, monobloc cast iron brake disc with fingered hub. Issue 10 (3rd October 2019) - Topouris, Stergios; Tirovic, Marko
ABSTRACT: This article focuses on generating a monobloc fingered hub (top-hat) disc design, aiming at reducing disc mass but maintaining rotor thermal capacity, while also improving heat dissipation characteristics. The analyses and tests demonstrated that such a design is possible to achieve, with mass reduction of just over 9%. The activities included research into cast iron modelling, which gave very important insights into the limits of mechanical performance under bending. Initial finite element analyses enabled considerable progress to be made towards establishing a baseline design, but only through shape optimization and topology optimization procedures was the full potential of the design accomplished. Shape optimization facilitated the reduction of maximum principal stress by 32%, considerably improving disc torsional strength with practically no increase in mass. The safety factor in torsion achieved a value of 3.57. Topology optimization provided further, although small, mass reduction (1.5%) while maintaining low stress levels.